Skin manifestations of tick bites in humans - Vidal Haddad Jr; Michel Raineri Haddad; Mônica Santos; João Luiz Costa Cardoso (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Ticks are blood-sucking arthropods that attach to human skin through oral devices causing diverse initial cutaneous manifestations, and may also transmit serious infectious diseases. In certain situations, the Health Teams (and especially dermatologists) may face difficulties in identifying the lesions and associating them to the parasites. To assist them in clinical diagnosis, we suggest a classification of the skin manifestations in primary lesions, which occur by the attachment the tick to the host (for toxicity and the anticoagulant substances in the saliva and/or marked inflammation by the penetration and permanence of the mouthparts) and secondary lesions that are manifestations of infections caused by rickettsia, bacteria, protozoa and fungi inoculated by the ticks.